The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1462-2920.2006.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Anammox bacteria disguised as denitrifiers: nitrate reduction to dinitrogen gas via nitrite and ammonium

Abstract: Anaerobic ammonium-oxidizing (anammox) bacteria oxidize ammonium with nitrite and produce N(2). They reside in many natural ecosystems and contribute significantly to the cycling of marine nitrogen. Anammox bacteria generally live under ammonium limitation, and it was assumed that in nature anammox bacteria depend on other biochemical processes for ammonium. In this study we investigated the possibility of dissimilatory nitrate reduction to ammonium by anammox bacteria. Physically purified Kuenenia stuttgartie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
318
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(352 citation statements)
references
References 34 publications
10
318
1
3
Order By: Relevance
“…Candidatus Kuenenia stuttgartiensis is a salt-and alkaline-resistant bacterium Strous et al 2006), and it was detected mostly in wastewater treatment system (Egli et al 2001;Schmid et al 2000). Previous research showed that anammox diversity was usually low in an ecosystem (Schmid et al 2007;Kartal et al 2007). In our bioreactor, anammox bacteria detected by qPCR accounted for 0.27 % of total bacteria, and the value was higher than that from the pyrosequencing method.…”
Section: Discussionmentioning
confidence: 99%
“…Candidatus Kuenenia stuttgartiensis is a salt-and alkaline-resistant bacterium Strous et al 2006), and it was detected mostly in wastewater treatment system (Egli et al 2001;Schmid et al 2000). Previous research showed that anammox diversity was usually low in an ecosystem (Schmid et al 2007;Kartal et al 2007). In our bioreactor, anammox bacteria detected by qPCR accounted for 0.27 % of total bacteria, and the value was higher than that from the pyrosequencing method.…”
Section: Discussionmentioning
confidence: 99%
“…This process has long been known to occur in sediments (Sørensen, 1978), and it has recently been observed in the water column of the Namibian oxygen minimum zone (Kartal et al, 2007). In the water column, DNRA may provide up to 100% of the ammonium utilized by anammox bacteria (Kartal et al, 2007;Lam et al, 2009), while in some coastal settings, DNRA is thought to be responsible for ~30% of all nitrate reduction (Giblin et al, 2013). It is therefore an important biogeochemical process.…”
Section: Dissimilatory Nitrate Reduction To Ammonium (Dnra)mentioning
confidence: 99%
“…Five Candidatus genera of anammox bacteria have been described: Brocadia (Kartal et al 2008), Kuenenia (Schmid et al 2000), Scalindua (Schmid et al 2003;Kuypers et al 2005), Anammoxoglobus (Kartal et al 2007), and Jettenia (Quan et al 2008). Each of these genera has been detected in coastal estuaries .…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%